Association of the ACTN3 R577X polymorphism with power athlete status in Russians - Druzhevskaya, A. M.; Ahmetov, I. I.; Astratenkova, I. V.; Rogozkin, V. A. (European Journal of Applied Physiology, 2008)
The a-actinin-3 (ACTN3) gene encodes a Z-disc structural protein which is found only in fast glycolytic muscle fibers. A common nonsense polymorphism in codon 577 of the ACTN3 gene (R577X) results in a-actinin-3 deficiency in XX homozygotes. Previous reports have shown a lower proportion of the ACTN3 XX genotype in power-oriented athletes compared to the general population. In the present study we tested whether XX genotype was under-represented in Russian power-oriented athletes. The study involved 486 Russian power-oriented athletes of regional or national competitive standard. ACTN3 genotype and allele frequencies were compared to 1,197 controls. The frequencies of the ACTN3 XX genotype (6.4 vs. 14.2%; P < 0.0001) and X allele (33.3 vs. 38.7%; P = 0.004) were significantly lower in power-oriented athletes compared to controls. Furthermore, the lowest (3.4%) frequency of the ACTN3 XX genotype was found in a group of highly elite athletes, supporting the hypothesis that the presence of a-actinin-3 has a beneficial effect on the function of skeletal muscle in generating forceful contractions at high velocity. In conclusion, ACTN3 R577X polymorphism was associated with power athlete status in Russians.